Optimization of metabolic demands in tennis training - Weber, K. (2000)
Performance standards are rising in top-level tennis (particularly in men`s competitions) and there is a growing need to optimize training. This study involved a total of 26 nationally-ranked tennis players who performed three different training drills aiming at technique stabilization (TS1: forehand-winner) and technique application (TA1: passing shot and TA2: forehand/backhand drill). For TS1, in comparison with series of four and twelve strokes, a series of eight strokes resulted in blood lactate concentrations similar to those found in match play (4.8±1.5 mmol.L-1), the highest hitting accuracy (45.5±7.2% valid) and the second-highest average ball velocity (124±5 km/h). For TA1, performing only one sprint before a passing shot produced the same lactate level as found in match play (4-6 mmol.L-1), whereas a series of two consecutive sprints led to a lactate acidosis, which rarely occurs in match play. For TA2, a series of four strokes produced lactate levels which remained within the range of maximum demands in tennis competition, whereas a series of six consecutive strokes led to a lactate level above the match play level (9.9±1.7 mmol.L-1). Levels of acidosis and stroke precision were negatively correlated (r=-0.677). A highly significant statistical correlation (r=0.774) was found between the quality of basic endurance (defined as running velocity at a lactate level of 4 mmol.L-1) and the lactate level during a forehand/backhand drill using eight balls. The conclusion is that monitoring guidelines (intensity, frequency and duration of workload) must be carefully selected in order to guarantee a realistic simulation of the energetic pathways, avoid fatigue and ensure optimization of technique and tennis-specific movement patterns.